PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN LABORATORIUM LABBIOGEN DI SURABAYA - Jois Fera Diana; Achmad Djoni Sudirman (Bisnis-Net, 2023)
This study aims to determine whether service quality and company image have an effect on customer satisfaction at the Labbiogen Laboratory in Surabaya. This research is a descriptive quantitative type with a population of 92 customers of Labbiogen Laboratory in the city of Surabaya and samples were obtained using a purposive sampling technique, where the criterion was that the customer had at least checked at least 2 times. The research data is primary data using a questionnaire which is distributed using a Google Form, which is done to avoid transmission of the Covid-19 virus. The results showed that: Service Quality and Corporate Image have a significant effect on Customer Satisfaction of the Labbiogen Laboratory in Surabaya, both partially and simultaneously. From the results of the coefficient of determination, the R2 value is 0.479 or 47.90%. This shows that customer satisfaction can be explained by 47.90% by the independent variables namely Service Quality and Company Image). While 52.10% of the variable Customer Satisfaction is explained by other variables outside the independent variables in this study.